PENINGKATAN KETERAMPILAN DASAR MENGAJAR MELALUI OPTIMALISASI RAGAM UMPAN BALIK - Eko Purwanti (JURNAL LITBANG PROVINSI JAWA TENGAH, 2009)
The purpose of this experiment is to improve the quality of basic competence teaching for students of PGSD UNNES. The way of improving this competence is done by the optimalization in many feed back activities to their work. The kinds of competence which is improved are basic skills in teaching such as: opening and closing the lesson, basic and further questioning, and class management. The purpose of the feed back activity is the improvement of the quality of simulation planning in basic skill teaching, the aplication of basic skill teaching observation quality, and the discussion about the result of basic skill teaching. This experiment method uses class action experiment planning, the aplication of action, the observation of action, and reflection. Those action procedures are in siclus. After it has done in three siclus in every individual, the achievements are the result of basic skill teaching in opening and closing the lesson improvement, basic and further questioning, and class management. The improvement of quality of basic competence skill teaching from poorly skill category to become well skill category. The conclusion is that using many various kinds of feed back activities can improve the quality of basic competence teaching in the students of PGSD UNNES.